Characterization of chelator‐mediated recovery of pancreatic islets from barium‐stabilized alginate microcapsules. (8th September 2019) - Rodriguez, Samuel; Lau, Hien; Corrales, Nicole; Heng, Jennifer; Lee, Sarah; Stiner, Rachel; Alexander, Michael; Lakey, Jonathan R. T.
Abstract: Introduction: Islet recovery from within alginate‐based microcapsules is necessary for certain analytical assays like flow cytometry; however, this technology has not been widely characterized. In this study, we explore the ability of EDTA, EGTA, and sodium citrate to induce reverse alginate polymerization via chelation and assess the toxicity of each chelator on pancreatic islets. Methods: EDTA, EGTA, and sodium citrate were used to dissolve single‐layered Ba 2+ alginate encapsulated islets and the rate of capsule breakdown calculated from analysis of imaging data. The effect of chelator exposure on islet viability and recovery was assessed using flow cytometry, while glucose‐stimulated insulin release (GSIR) assay was used to measure effects on islet function. Results: EGTA demonstrated the most rapid microcapsule dissolving rate followed by EDTA and sodium citrate. Islet recovery was significantly better when encapsulated islets were treated with EDTA than EGTA and Na + citrate. A decrease in viability and increase in apoptotic cells were observed when encapsulated islets were treated with Na + citrate compared to islets treated with EDTA and EGTA. Islets treated with EDTA and EGTA demonstrated comparable stimulation index values to non‐treated control. Conversely, islets treated with Na + citrate exhibited significantly decreased SI values compared to control. All chelator groups showed significantly lower insulin secretion than non‐treated islets. Conclusion: Islet recovery from alginate microcapsule is possible using common chelators like Na + citrate, EDTA, and EGTA. Chelation of encapsulated islets using EDTA demonstrated the most efficient dissolving capabilities with the least toxicity toward islet recovery and health.